Simplifying perovskite solar cell fabrication for materials testing: how to use unetched substrates with the aid of a three-dimensionally printed cell holder - Valdez García, Joaquín; Hadadian, Mahboubeh; Nizamov, Rustem; Mäkinen, Paavo; Lamminen, Noora; Vivo, Paola; Miettunen, Kati (Royal Society Publishing, 2026)
This work demonstrates that unetched substrates can be reliably used in perovskite solar cell (PSC) fabrication. Chemical etching and laser patterning of the bottom electrodes are time- and resource-consuming processes. In particular, when testing novel conductive substrate materials, such as metallic or bio-based substrates, etching or patterning could be entirely unfeasible or could require significant process optimization. Avoiding these steps could accelerate research on PSCs, yet the literature shows no attempts to override these steps. Here, PSCs were fabricated and characterized using three-dimensionally printed holders with spring-loaded pins. We show that devices made on unetched substrates have, on average, a similar performance to those made on etched substrates (16 ± 1% and 16.0 ± 0.7%, respectively). Our study provides a new strategy for fabricating PSCs, particularly when etching and laser patterning are impractical.